The powers of a social auditor in a global production network: the case of Verité and the exposure of forced labour in the electronics industry - Gale Raj-Reichert (Journal of Economic Geography, 2020)
Research on labour governance actors in global production networks (GPNs) has been limited to civil society organisations, firms and governments. Understanding the influence of actors in GPNs has been dealt with singular and overt modes of relational power. This paper contributes to both debates by examining an intermediary actor—the social auditing organisation Verité—and its exercise of multiple modes of overt and covert powers to illustrate the complex terrain of change in GPNs. Verité, whose exposure of forced labour in Malaysian electronics subsequently changed labour governance practices in the electronics industry, mobilised power resources of credible information to exercise powers of expert authority and acts of dissimulation across various networked relationships in the GPN. This paper puts forth a multi-power framework of analysis to understand the micro-politics of GPNs.
Keywords: 330; power; social auditor; forced labour; global production network